Lipid Droplets, the Central Hub Integrating Cell Metabolism and the Immune System - Zhang, Wei; Xu, Linyong; Zhu, Ling; Liu, Yifan; Yang, Siwei; Zhao, Mingyi (Frontiers in Physiology, 2021)
Lipid droplets (LDs) are commonly found in various biological cells and are organelles related to cell metabolism. LDs, the number and size of which are heterogeneous across cell type, are primarily composed of polar lipids and proteins on the surface with neutral lipids in the core. Neutral lipids stored in LDs can be degraded by lipolysis and lipophagocytosis, which are regulated by various proteins. The process of LD formation can be summarized in four steps. In addition to energy production, LDs play an extremely pivotal role in a variety of physiological and pathological processes, such as endoplasmic reticulum stress, lipid toxicity, storage of fat-soluble vitamins, regulation of oxidative stress, and reprogramming of cell metabolism. Interestingly, LDs, the hub of integration between metabolism and the immune system, are involved in antitumour immunity, anti-infective immunity (viruses, bacteria, parasites, etc.) and some metabolic immune diseases. Herein, we summarize the role of LDs in several major immune cells as elucidated in recent years, including T cells, dendritic cells, macrophages, mast cells, and neutrophils. Additionally, we analyse the role of the interaction between LDs and immune cells in two typical metabolic immune diseases: atherosclerosis and Mycobacterium tuberculosis infection.